Chronic Pancreatitis Correlates With Increased Risk of Cerebrovascular Disease: A Retrospective Population-Based Cohort Study in Taiwan. Issue 15 (April 2016) - Wong, Tuck-Siu; Liao, Kuan-Fu; Lin, Chi-Ming; Lin, Cheng-Li; Chen, Wen-Chi; Lai, Shih-Wei
Abstract : Abstract: The aim of this study is to explore whether there is a relationship between chronic pancreatitis and cerebrovascular disease in Taiwan. Using the claims data of the Taiwan National Health Insurance Program, we identified 16, 672 subjects aged 20 to 84 years with a new diagnosis of chronic pancreatitis from 2000 to 2010 as the chronic pancreatitis group. We randomly selected 65, 877 subjects aged 20 to 84 years without chronic pancreatitis as the nonchronic pancreatitis group. Both groups were matched by sex, age, comorbidities, and the index year of diagnosing chronic pancreatitis. The incidence of cerebrovascular disease at the end of 2011 was measured. The multivariable Cox proportional hazards regression model was used to measure the hazard ratio (HR) and 95% confidence interval (CI) for cerebrovascular disease risk associated with chronic pancreatitis and other comorbidities. The overall incidence of cerebrovascular disease was 1.24-fold greater in the chronic pancreatitis group than that in the nonchronic pancreatitis group (14.2 vs. 11.5 per 1000 person-years, 95% CI = 1.19–1.30). After controlling for confounding factors, the adjusted HR of cerebrovascular disease was 1.27 (95% CI = 1.19–1.36) for the chronic pancreatitis group as compared with the nonchronic pancreatitis group. Woman (adjusted HR = 1.41, 95% CI = 1.31–1.51), age (every 1 year, HR = 1.04, 95% CI = 1.04–1.05), atrial fibrillation (adjusted HR = 1.23, 95% CI = 1.02–1.48), chronic kidney disease (adjusted HR = 1.48, 95% CI = 1.31–1.67), chronic obstructive pulmonary disease (adjusted HR = 1.27, 95% CI = 1.16–1.40), diabetes mellitus (adjusted HR = 1.82, 95% CI = 1.72–1.92), hypertension (adjusted HR = 1.66, 95% CI = 1.56–1.76), and peripheral atherosclerosis (adjusted HR = 1.26, 95% CI = 1.06–1.51) were other factors significantly associated with cerebrovascular disease. Chronic pancreatitis is associated with increased hazard of subsequent cerebrovascular disease.